Transient Modelling of Solid Oxide Cell Modules and 50 kW Experimental Validation. (10th July 2019) - Tomberg, Marius; Santhanam, Srikanth; Heddrich, Marc P.; Ansar, Asif; Friedrich, Kaspar Andreas
Abstract : Solid oxide cells (SOC) can be a major contributor to shaping the future energy system. To achieve this, SOC plants containing large reactor modules have to reach the megawatt and multi-megawatt scale. Moving from individual stacks to these large modules is challenging. Therefore, this contribution addresses investigations of large SOC modules that consist of tens or even hundreds of stacks, manifolds, piping and insulation. Experimental results show that the individual stacks of a module work under different operating conditions due to their spatial location. In order to investigate and predict these different operating conditions, a module model is being developed. This paper explains the development of a reactor module model from a detailed one-dimensional cell model. Subsequently, an exemplary simulation result is presented and the next steps are described.